Role of polymorphisms of folate-cycle enzymes in diabetic retinopathy progression in patients with type 2 diabetic mellitus - S. O. Rykov; Iu. V. Prokopenko; L. V. Natrus; Iu. O. Panchenko (Ukrainian Society of Ophthalmologists, 2022)
Background: Hyperhomocysteinemia is important in the development of endothelial dysfunction, a pathogenetic component of diabetic retinopathy (DR) in type 2 diabetes mellitus (DM2). The major cause of homocysteine accumulation is missing or dysfunctional enzymes and cofactors that are needed to perform homocystein metabolic processes. This is, for the most part, the deficiency of folate cycle enzymes determined by methylenetetrahydrofolate reductase (MTHFR) C677T, MTHFR A1298C, and methionine synthase (MTR) A2756G polymorphisms. Purpose: To assess the role of polymorphisms of folate cycle enzymes (MTHFR C677T, MTHFR A1298C, MTR A2756G) in DR progression in patients with DM2. Material and Methods: The study included 83 DM2 patients (83 eyes) in whom DR met the criteria of non-proliferative diabetic retinopathy (NPDR) or proliferative diabetic retinopathy (PDR) according to the Early Treatment of Diabetic Retinopathy Study (ETDRS). The control group was composed of 35 non-diabetics comparable to patients with respect to gender, age and body mass index. Real-time PCR was conducted on a Gene Amp® PCR System 7500 to determine polymorphisms. Plasma L-homocysteine levels were determined using an enzyme-linked immunosorbent assay (ELISA) microplate reader and Axis® Homocysteine Enzyme Immunoassay Kit (AXIS-SHIELD Diagnostics Ltd). Conclusion: We found no association of rs1801133, rs1805087, and rs1801131, folate-cycle polymorphisms, with the development of DR in DM2, compared with non-diabetics. In NPDR patients having the minor homozygous GG genotype of MTR 2756А/G and/or the minor homozygous CC genotype of MTHFR 1298A/C, plasma L-homocysteine levels were significantly increased. This requires further elucidation of the role of hyperhomocysteinemia as a factor of DR progression or as a marker of the severity of tissue injury. The duration of DM2 is an important factor of DR progression in carriers of the most common CC and CT genotypes of rs1801133, AG genotype of rs1805087, and АА genotype of rs1801131.